2018
DOI: 10.1186/s12889-018-6148-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of exposure to second hand smoke (SHS) among 14 to 15 year old schoolchildren in a medical officer of health area in Sri Lanka

Abstract: BackgroundDespite reports that Southeast Asia has one of the highest prevalence for childhood exposure to second hand smoke (SHS), there are limited data on SHS exposure among schoolchildren in individual countries in the region, including Sri Lanka. This study aimed to determine the prevalence and correlates of SHS among schoolchildren in a Medical Officer of Health (MOH) region in the country.MethodsWe conducted a cross-sectional study, sampling from nice schools in one MOH region following a two-stage clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our findings indicate factors associated with the initiation of tobacco smoking in this age group include sociodemographic factors, family-related factors, and especially the factors related to media use. These factors are associated with the ethnic, religious, and cultural background of adolescents and are known to play a major role in risks associated with their smoking behaviour [18] In the current study, none of the Muslim students had ever smoked. It was a significant finding in the bivariate analysis.…”
Section: Open Accessmentioning
confidence: 57%
“…Our findings indicate factors associated with the initiation of tobacco smoking in this age group include sociodemographic factors, family-related factors, and especially the factors related to media use. These factors are associated with the ethnic, religious, and cultural background of adolescents and are known to play a major role in risks associated with their smoking behaviour [18] In the current study, none of the Muslim students had ever smoked. It was a significant finding in the bivariate analysis.…”
Section: Open Accessmentioning
confidence: 57%
“…The study results are also consistent with the overall prevalence of exposure to SHS in low- and middle-income countries being 55.9%, varying from 16.45% in Tajikistan to 85.4% in Indonesia [ 15 ]. In Sri Lanka, the prevalence of exposure to SHS during the previous week was 17.6% at home and 25.7% in enclosed public places [ 31 ]. However, some countries have reported higher exposures, such as Malaysia [ 32 ] and Thailand [ 33 ] at 56.4% and 48.6%, respectively, although in the Malaysian study it is not clear whether the results refer to SHS exposure at home or also include other places.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because unskilled workers are less educated, may not be aware of the risks of SHS exposure and may also spend more time at home due to the uncertainty in their job. A similar study in Ernakulam found that father's lower educational status was an important determinant [ 29 ] and in Sri Lanka, mother's unemployment status was a significant determinant of exposure to SHS, which could also be a proxy for lower educational status [ 31 ]. The vulnerable population in the lower rungs of socioeconomic status appear to be impacted to a greater extent by SHS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the outdoor environment was divided into two groups, namely inside the car and public space, in the present study, the total exposure in these two environments was 54.7, which is consistent with the above survey. In a study conducted in Sri Lanka in 2018, the findings suggested that exposure to SHS in this country was higher in public places than at home [ 25 ].…”
Section: Discussionmentioning
confidence: 99%